Implementation Of Integrated Assessment In Law Enforcement Against Drug Abusers Narcotics - Zainal; Syaiful Asmi Hasibuan (ASIAN PUBLISHER, 2023)
The Narcotics Law aims to ensure the regulation of medical and social rehabilitation efforts for drug abusers and addicts. In law enforcement, drug abusers are not necessarily rehabilitated but must first go through an integrated assessment process. The problem in this study is how the application of integrated assessment in law enforcement against drug abusers and why there are obstacles in the application of integrated assessment in law enforcement against drug abusers. This research uses normative juridical and empirical juridical approaches, namely by reading and quoting from literature books and interviews with respondents consisting of Integrated Assessment Team Members. Based on the results of the research and discussion, the application of integrated assessment is based on the provisions of the Joint Regulation of 7 (seven) State Institutions as a technical guideline for the establishment and operation of the Integrated Assessment Team consisting of a Medical Team to identify the level of addiction and a Legal Team to investigate the involvement of abusers with the narcotics trafficking network. The implementation of integrated assessments results in recommendations regarding placement plans into rehabilitation installations which also become court documents as a consideration for judges in deciding cases. The obstacles that occur are generally caused by law enforcement factors that still have different perceptions in determining the application of assessments of drug abusers and facilities and infrastructure factors in carrying out law enforcement against drug abusers.